Detection of hemizygosity at the elastin locus by FISH analysis as a diagnostic test in both classical and atypical cases of Williams syndrome. Issue 9 (September 1995) - Borg, I; Delhanty, J D; Baraitser, M
Abstract : A small pilot study has been carried out in order to assess the reliability of the detection of hemizygosity at the elastin locus by fluorescence in situ hybridisation (FISH) analysis, as a diagnostic test in both classical and atypical cases of Williams syndrome (WS). Five subjects with WS and five others in whom a diagnosis could not be confirmed on clinical criteria alone were evaluated. Hemizygosity at the elastin locus by FISH analysis was detected in all classical Williams syndrome cases and in three of the five atypical subjects. Furthermore, a combination of a few specific facial features found to be present in all subjects with the elastin gene hemizygosity has been suggested to aid the index of clinical suspicion.